Novo modelo de pancreatite crônica alcoólica em murinos: Aspectos inflamatórios, hiperalgesia visceral e fibrogênese - Franco, Alvaro Xavier (2019)
Chronic pancreatitis (CP) is a progressive inflammatory disease characterized by irreversible morphological changes of the pancreas.The inflammatory process is persistent after deletion of deleterious factors and the pancreatic parenchyma is replaced by fibrous tissue, leading to loss of function.The characterization of a model of chronic alcoholic pancreatitis investigating the inflammatory aspects, hyperalgesia and fibrinogenesis, provides the understanding of its pathophysiology.Experimental chronic pancreatitis induced in Swiss mice, separated in control group and POA groups 1, 21, 29 and 44 days, with doses of palmitoleic acid (POA) associated to ethanol (1.35 g / kg) at concentrations of 150 , 75 and 37.5 mg / kg intraperitoneally with an interval of 1 (one) hour between the applications.The animals were euthanized and blood, faeces and pancreas were collected for biochemical analyzes (amylase, lipase, glucose, trypsin, MPO and α-SMA) and histopathology (glandular atrophy, fibrosis and monocellular cell infiltration).The survival of animals with experimental chronic pancreatitis was on average 56.06% and pancreatic tissue replacement was observed by fibrosis. There were alterations of important biochemical enzymes in lipase, glucose, trypsin, myeloperoxidase, Sudam III and presence of increased expression of α-SMA, a marker in the stellate cell that participate in the fibrosis process. Alterations in the nociceptive threshold were observed, persistent at the last experimental period. The application of POA associated with intraperitoneal ethanol consists of a new model with evidence of structural, biochemical and functional changes described in clinical practice, evidencing investigations and perspectives for studies of the pathophysiology of this disease, as well as new pharmacological modulation strategies.